THE EFFECT OF INTELLECTUAL CAPITAL, CORPORATE GOVERNANCE, GENDER OF DIRECTORS, AGE OF DIRECTORS, AND EDUCATIONAL BACKGROUND OF DIRECTORS TOWARDS FINANCIAL PERFORMANCE - Andra Tiara Syafira; Bima Cinintya Pratama; Hadi Pramono; Rina Mudjiyanti (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The purpose of this study is to find out the effect of Intellectual Capital, Corporate Governance, Gender of Directors, Age of Directors, and Educational Background of Directors towards Financial Performance. The population used in this study is banking companies in 2017-2020. The sampling technique used is the purposive sampling technique so that a sample of 164 companies met the criteria. The results showed that the Intellectual Capital variable had a positive effect towards Financial Performance, and the Age variable of the Board of Directors negatively affected Financial Performance. While the variables of Corporate Governance, Gender of Directors, and Educational Background of the Board of Directors have no effect towards Financial Performance